Evaluating Preoperative Anxiety Levels in Patients Undergoing Breast Cancer Surgery - Katsohiraki, Maria (Asia Pac J Oncol Nurs, 2020)
OBJECTIVE: Patients' anxiety and stress levels are increased after the surgery. High levels of anxiety and stress could increase postoperative complications, as well as to prolong postoperative hospitalization and postoperative morbidity. This prospective, cross-sectional study was to evaluate the preoperative stress levels in patients undergoing breast cancer surgery. METHODS: In the study participated 165 female patients who underwent breast cancer surgery, in a major oncological hospital in Greece. Demographic and clinical data were collected, and anxiety and stress levels assessed using the State-Trait Anxiety Inventory (STAI) Scale, which was a self-report questionnaire consisting of 40, 4 Likert Scale questions. The first 20 questions, STAI-X-1, were concerned to how the patient felt while answering the questionnaire (anxiety as a condition) and the remaining 20 questions, STAI-X-2, based on how the patient felt overall (stress as a personality trait). Descriptive statistics and nonparametric tests were performed at a significance level alpha = 0.05. RESULTS: In the present study, 165 females were enrolled who underwent breast cancer surgery. The mean age of the participants was 55.86 years, whereas the mean body mass index was 26.85. The 60.6% of patients underwent a lumpectomy and 28.5% had mastectomy. The 35.8% experienced moderate levels of anxiety, and the 17.6% experienced high levels. The two scales were positively correlated (rho = 0.643, P < 0.001), at the significance level P = 0.01. Furthermore, the Stai-X-2 Scale was negatively correlated with body height (rho = −0.1188, P = 0.016). CONCLUSIONS: The present study showed that patients' personality influenced their anxiety levels. Thus, the role of the nurse is a cornerstone in their psychological support preoperatively, to reduce the anxiety and stress levels.